ANALISIS SEMIOTIKA PADA PUISI “BARANGKALI KARENA BULAN” KARYA WS. RENDRA - Budi Setia Pribadi; Dida Firmansyah (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Poetry is an expression of the soul through anesthetic words. Poetry can also be interpreted as the oldest literary work that has the beauty of the words used in each verse. Poetry has two main structures of builders, namely: inner structure and physical structure. Besides that, in a poem, there are several markers, both in the form of meanings that need to be translated by the reader and linguistic markers that do not require reinterpretation. Field of study that studies and examines markers, symbols, and signal in a field of study, called semiotics. Semiotic is a scientific study that studies the signs that exist in a literary work. Understanding of semiotics needs to be done by literary activists because a poem must contain a marker as an aesthetic literary work. The study of poetry through the realm of semiotics becomes more interesting because how to study discusses how studying a poem by enjoying its markers. From that marker, poetry is built into an authentic work and has the beauty of the language contained in it. Semiotics has an important role in building a poem can provide a picture and understanding to the reader. Hence from that semiotic is very important to be studied and understood, because language and semiotics cannot be released.